Risk Prevention of Ventilator-Associated Pneumonia Thorough Oral Hygiene: A Literature Review - Musdalipah, Musdalipah; Syam, Yuliana; Tahir, Takdir (The Journal of Experimental Life Science, 2021)
Ventilator-Associated Pneumonia (VAP) is a type of nosocomial infection that mostly occurs in intensive care units, generally occurring 48 hours after intubation. Endotracheal intubation and the use of a mechanical ventilator are invasive measures by patients, having a therapeutic effect. This paper aimed to identify the use of oral hygiene materials for the incidence of pneumonia related to the use of a ventilator. The research design was by searching literature in five databases, namely PubMed, Proquest, Science Direct, Wiley Online Library, and Google Scholar, by taking all databases in English and Indonesian, published in the last ten years (2010-2020). There were six articles about the effectiveness of using oral hygiene as risk prevention for Ventilator-Associated Pneumonia (VAP) with various concentrations and volumes. Several oral health assessment tools that can be used are Oral Assessment Guide, Beck Oral Assessment Scale, or Mucosal-Plaque Score. Comprehensive implementation of oral hygiene can improve the oral health of patients with mechanical ventilation, so bacterial colonization that causes VAP can be prevented. Therefore, nurses need to understand and apply oral assessment instruments as a basis for giving intervention.Keywords: Intensive care unit, Oral hygiene, Ventilator-Associated Pneumonia